Diagnostic Performance of Urine-based HPV-DNA Test (CerviScan, Bio Farma) as Cervical Cancer Screening Tool in Adult Women: Performa Tes Diagnostik DNA-HPV berbasis Urine (CerviScan, Bio Farma) sebagai Alat Skrining Kanker Serviks pada Perempuan Dewasa - Andrijono Andrijono; Dewi Wulandari; Indah Suci Widyahening; Dicky Mahardhika; Neni Nurainy; Rini Mulia Sari; Indriastuti Soetomo; Revata Utama (Indonesian Journal of Obstetrics and Gynecology, 2023)
Objective: Detection of high-risk human papillomavirus (hr-HPV) in urine specimens has been introduced recently and a new local PCR kit has been developed in Indonesia (CerviScan, Bio Farma). The objective of this study was to obtain the accuracy of hr-HPV DNA testing using the new kit (CerviScan, Bio Farma) on urine specimens against the gold standard on cervical swabs.Method: Adult women (aged 20–50 years) underwent routine general check-up or Pap test were enrolled between July and September 2022. Pairs of urine and cervical swab specimens were obtained from all subjects. HPV-DNA tests were performed using the new local PCR kit (CerviScan, Bio Farma) and the standard procedure (COBAS® 6800 HPV, Roche Molecular System). Direct sequencing was added whenever there were dispute results between the two methods. Agreement between both methods was tested using Kappa statistics. Diagnostic performance test was done on CerviScan. Results: A total of 876 women completed the examination. Agreement between CerviScan and COBAS® 6800 was substantial (K=0.662; p<0.001) and was almost perfect against COBAS® 6800 plus sequencing (K=0.828; p<0.001). The accuracy of CerviScan on urine samples was 95.8% against COBAS® 6800 and increased to 97.8% after additional sequencing. The sensitivity and specificity of CerviScan on urine samples compared to cervical swabs are 73.1% and 97.3%, respectively.Conclusion: Urine-based HPV-DNA testing with CerviScan is a reliable tool to detect high-risk HPV subtypes. It could become an alternative method for HPV-DNA testing to improve the coverage of cervical cancer screening program.